Energetic-exergetic-economic analyses of a cogeneration thermic power plant in Turkey - Can, Omer F.; Celik, Nevin; Dagtekin, Ihsan (Pergamon-Elsevier Science Ltd, 2009)
In present study the exergy and economical analysis of a cogeneration plant system in Turkey (Esenyurt Thermic Power Plant) was performed based on the measured data during the operation time of the system. First and second laws of thermodynamics are adapted to the measured data. Furthermore, fuel-utilization efficiency, rate of power heat and rate of process heat are determined. The system is considered as a steady-state open thermodynamic system. As a result, it is found that the second law efficiency is 89.5% which is accepted as an agreeable value in archival journals. The pay back period of the plant is found 3.5 years, which is favorable time period for well designed plants in terms of the economical analysis. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Exergy analysis; Cogeneration plant; Second-law analysis